2006
DOI: 10.2307/40035887
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Archaeological Verification of an Index of Retouch for Hafted Bifaces

Abstract: The relative amount of retouch on stone tools is central to many archaeological studies linking stone tool assemblages to broader issues of human social and economic land-use strategies. Unfortunately, most retouch measures deal with flake and blade tools and few (if any) have been developed for hafted bifaces and projectile points. This paper introduces a new index for measuring and comparing amount of retouch on hafted bifaces and projectile points that can be applied regardless of size or typological varian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(50 citation statements)
references
References 38 publications
0
48
0
2
Order By: Relevance
“…With the exception of variability attributable to the physical properties of conchiodal fracture, it could be argued that other sources of variability, at all geographic and temporal scales, are determined by the archaeological context in which the stone artifacts are found, an observation that is partly subsumed within the study of technological organization (e.g., Andrefsky 2006;Binford 1973Binford , 1977Kelly 1988;Nelson 1991;Torrence 1983) but one that following comments on the philosophy of archaeology (e.g., Kosso 1991;Fogelin 2007) is also consistent with the postprocessual discussions of context and meaning generated through action (particularly Hodder 1999:77, 84-92). In the Australian ethnographic studies discussed above, Aboriginal people had a range of responses to the need to manufacture and use stone artifacts.…”
Section: Contextsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the exception of variability attributable to the physical properties of conchiodal fracture, it could be argued that other sources of variability, at all geographic and temporal scales, are determined by the archaeological context in which the stone artifacts are found, an observation that is partly subsumed within the study of technological organization (e.g., Andrefsky 2006;Binford 1973Binford , 1977Kelly 1988;Nelson 1991;Torrence 1983) but one that following comments on the philosophy of archaeology (e.g., Kosso 1991;Fogelin 2007) is also consistent with the postprocessual discussions of context and meaning generated through action (particularly Hodder 1999:77, 84-92). In the Australian ethnographic studies discussed above, Aboriginal people had a range of responses to the need to manufacture and use stone artifacts.…”
Section: Contextsmentioning
confidence: 99%
“…If technology is situational, then diagnosing why one particular technological solution was adopted where and when it was requires a comparative analysis, an approach increasingly provided by studies of technological organization (e.g., Andrefsky 2006;Binford 1973Binford , 1977Kelly 1988;Nelson 1991;Torrence 1983) as well as ethnoarchaeological studies (e.g., Arthur 2010;Weedman 2006). But as the Australian ethnographic accounts illustrate, there is no easy way to determine which categories of artifact best illustrate the operation of technological organization based on artifact morphology alone.…”
Section: Complexitymentioning
confidence: 99%
“…It has been shown that using several retouch measures is preferred as different techniques reflect different dimensions of reduction (Eren et al 2005;Andrefsky 2006). The amount of retouch for this study was calculated using two measures.…”
Section: Stone Tool Retouch and Raw Materials Availabilitymentioning
confidence: 99%
“…methods for estimating the amount or effects of mass removed from a flake or tool by retouch or resharpening-has received extensive coverage in the literature (Andrefsky 2006;Bradbury, Carr, and Randall Cooper 2009;Braun et al 2010;Clarkson 2002;Davis and Shea 1998;Eren et al 2005; Eren and Prendergast 2008; Eren and Sampson 2009;Hiscock and Clarkson 2005;Horowitz and McCall 2013;Patten 2005;Shott et al 2000Shott et al , 2007Marwick 2008;Morales, Lorenzo, and Vergès 2015;Wilson and Andrefsky 2008), but with some exceptions, it has not been intensive. Rather, researchers have focused on using an experiment for the purpose of proposing new or newly revamped methods rather than for thoroughly vetting methods and validating that they actually work for their asserted purpose (Shott et al 2007:205-206).…”
Section: Replication As Methods Validationmentioning
confidence: 99%